Baicalin Inhibits Influenza A Virus Infection via Promotion of M1 Macrophage Polarization - Geng, Ping; Zhu, Haiyan; Zhou, Wei; Su, Chang; Chen, Mingcang; Huang, Chenggang; Xia, Chengjie; Huang, Hai; Cao, Yiou; Shi, Xunlong (Frontiers in Pharmacology, 2020)
Background and Aims: The natural compound Baicalin (BA) possesses potential anti-influenza virus activity. However, whether or not macrophage is involved in baicalin’s anti-viral effects and the underlying mechanisms remain unclear, which would be investigated in this study. Methods: In H1N1 A virus-infected mice and cells, macrophage recruitment, functional phenotype (M1/M2), and cell metabolism were carried out by flow cytometry, qRT-PCR, immune-fluorescence, Transwell system, and GC-MS based metabolomics Results: BA reduced approximately 90% recruitment of macrophage (CD11b+/F480+), meanwhile increased the proportion of M1 polarized macrophages in the bronchoalveolar lavage fluid (BALF) of infected mice. BA-stimulated macrophage M1 phenotype shift was further verified by detecting the macrophage M1 polarization signals (CD86 positive, iNOS positive, TNF-α, and iNOS/Arg-1 bias) in vitro cell systems (Ana-1 and primary peritoneal macrophage cells). Meanwhile, the activated IFN signals (upregulated IFN-β and IRF-3), apparent IL-1β cleavage, inhibited influenza virus replication (M gene), and discriminative cellular metabolic responses occurred in BA-treated cells. Conclusion: Baicalin triggered macrophage M1 polarization, IFN signals, and other cellular reactions, which were beneficial for fighting against H1N1 A virus infection.